A New Absolute Phase Detection Scheme - Sukkharak Saechia; Chusit Pradabpet; Jeerasuda Koseeyaporn; Paramote Wardkein (My University, 2016)
In this paper, the new absolute phase detection scheme (APDS) is presented. With a simple mathematical analysis, the proposed APDS algorithm is capable of accurately detecting the absolute phase without using reference phase like other conventional techniques. The other massive benefit of using the proposed APDS scheme is its range-expansion flexibility for each application depending on the selected traditional PD. Based on the proposed APDS, BPSK and QPSK demodulated simulations, accurately recovering 16-bit-information data, are implemented with the blind carrier recovery methods. Also, the analog multiplier PD was selected in order to verify the proposed QPSK demodulator under the AWGN channel. It is found that the output phase is irrelevantly disturbed by additive white Gaussian noise. For the QPSK-demodulated PSPICE simulation, the proposed technique is more compatible with the frame processing manner rather than the real time processing. From both PSPICE and Matlab simulations for BPSK and QPSK demodulation the proposed APDS scheme provides convenience, advantages, and acceptable results in comparison to other traditional techniques.
Keywords: APDS; Absolute phase; Optical Network Technologies